2011
DOI: 10.1128/jb.01401-10
|View full text |Cite
|
Sign up to set email alerts
|

Autoregulatory Characteristics of a Bacillus anthracis Serine/Threonine Kinase

Abstract: BA-Stk1 is a serine/threonine kinase (STK) expressed by Bacillus anthracis. In previous studies, we found that BA-Stk1 activity is modulated through dephosphorylation by a partner phosphatase, BA-Stp1. In this study, we identified critical phosphorylation regions of BA-Stk1 and determined the contributions of these phosphodomains to autophosphorylation and substrate phosphorylation. The data indicate that BA-Stk1 undergoes trans-autophosphorylation within a regulatory domain, referred to as the activation loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…2A and 2B). This result was in contradiction with 222 the earlier reports wherein B. anthracis prkC disruption was shown have no effect on the 223 bacterial growth in vitro (Shakir et al, 2010;Bryant-Hudson et al, 2011;Arora et al, 2017). 224…”
Section: Prkc Regulates the Expression Of Sap Ea1 And Bslo 177mentioning
confidence: 68%
“…2A and 2B). This result was in contradiction with 222 the earlier reports wherein B. anthracis prkC disruption was shown have no effect on the 223 bacterial growth in vitro (Shakir et al, 2010;Bryant-Hudson et al, 2011;Arora et al, 2017). 224…”
Section: Prkc Regulates the Expression Of Sap Ea1 And Bslo 177mentioning
confidence: 68%
“…Additionally, we expected to observe phosphorylation in the putative activation loop, as this has been observed for the PASTA kinases in M . tuberculosis and Bacillus anthracis [58,59]. Although we did observe a quadruply phosphorylated fragment ion that contained the putative loop region, the large size of the fragment ion prevented our ability to map specific phosphorylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…The blots were developed using the SuperSignal West Pico Chemiluminescent Substrate kit (Pierce) according to the manufacturer's instructions. Autophosphorylated PrkC was kept as a negative control for the ␣-Tyr(P) blot because it has been reported to be phosphorylated on Ser and Thr residues (30). Phosphorylated myelin basic protein (MyBP) phosphorylated by the Tyr kinase Abl (New England Biolabs) was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…PrkC is the only characterized STPK in B. anthracis and B. subtilis (28,29). Recent data showed that the loss of this enzyme (called BA-Stk1) in B. anthracis had profound effects on virulence (29,30). Furthermore, it was found that germinating spores of B. subtilis use degraded peptidoglycan fragments called "muropeptides" as a germination signal, which is sensed by C-terminal penicillin-binding protein and Ser/Thr kinaseassociated (PASTA) domains of PrkC (31).…”
mentioning
confidence: 99%